NEW UZBEKISTAN – A NEW SPIRITUAL SPACE (Scientific journal of the Fergana State University, 2025)
New Uzbekistan is establishing itself as a unique country with its own program of distinctive social-political and spiritual renewal amid global changes. The deep reforms and transformational political changes taking place in our country are aligned with contemporary world civilization. Based on the idea of "From a Strong State to a Strong Civil Society," the interests of individuals, as well as their rights, freedoms, and national and spiritual values, are increasingly being reinforced in New Uzbekistan.